2004
DOI: 10.1038/sj.npp.1300491
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Working Memory by Dopamine D4 Receptor in Rats

Abstract: Working memory is regulated by neurotransmitters in prefrontal cortex (PFC), including dopamine and norepinephrine. Previous studies of dopamine function in working memory have focused on the D 1 and D 2 receptors, with most evidence suggesting a dominant role for the D 1 receptor. Since the dopamine D 4 receptor is highly expressed in PFC, we hypothesize that it may also contribute to working memory. To test this hypothesis, we examined behavioral effects of L-745,870, a highly selective, centrally active, D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 52 publications
5
42
1
Order By: Relevance
“…D 4 receptor antagonist effects of clozapine may contribute the differential effects seen in the fimbria-fornixlesioned and sham-operated rats in the current study. Zhang et al (2004) found that a selective D 4 receptor antagonist impaired working memory performance in rats performing at high levels of accuracy, but improved working memory performance in rats with poor baseline performance levels. This is similar to the finding in the current study.…”
Section: Clozapine Effects At Diverse Receptorsmentioning
confidence: 95%
“…D 4 receptor antagonist effects of clozapine may contribute the differential effects seen in the fimbria-fornixlesioned and sham-operated rats in the current study. Zhang et al (2004) found that a selective D 4 receptor antagonist impaired working memory performance in rats performing at high levels of accuracy, but improved working memory performance in rats with poor baseline performance levels. This is similar to the finding in the current study.…”
Section: Clozapine Effects At Diverse Receptorsmentioning
confidence: 95%
“…We propose, on the basis of the functional properties and expression of ErbB4 and D4Rs in PV+ interneurons in the dorsal lateral prefrontal cortex (21,25) and hippocampus (this study), as well as their effects on KA-induced γ oscillations and plasticity (18,19), that these receptors are well situated to modulate network activity that impacts cognition. The fact that D4R-specific antagonists were found to be ineffective as antipsychotics for the treatment of schizophrenia (44,45) does not negate the potential use of D4R targeting drugs to treat cognitive deficits, as suggested by studies in primates and rodents (39,40,46,47). The colocalization of D4 and ErbB4 receptors on PV+ interneurons, activity of which is critically important for regulating excitatory/inhibitory balance and cognitive functions (31), perhaps by optimizing "signal-tonoise" ratio of cortical microcircuits (15), makes these receptor systems attractive targets for modulating network activities that underlie cognition.…”
Section: Significance Of Erbb4 and D4 Receptor Expression In Pv+ Gabamentioning
confidence: 99%
“…Follow-up work indicates that the contribution of DA to spatial working memory is mediated by the D 1 (Arnsten et al, 1994;Sawaguchi and Goldman-Rakic, 1991) and D 2 families of receptors (Arnsten et al, 1995;Zhang et al, 2004) that may influence mnemonic and response aspects of information processing within primate PFC (Wang et al, 2004;Williams and Goldman-Rakic et al, 1995). Other research attests to the importance of NA transmission, and the balanced activity of a 1 -and a 2 -adrenoceptors, in protecting the cognitive functions of the lateral PFC from the deleterious effects of stress (Arnsten, 2000;Arnsten and Contant, 1992;Arnsten and Jentsch, 1997;Birnbaum et al, 2000).…”
Section: Introductionmentioning
confidence: 99%